ADOPTION OF SMALL RUMINANTS’ FATTENING PACKAGE IN AGRO-PASTORAL AREAS, DUGDA DAWA DISTRICT, SOUTHERN OROMIA, ETHIOPIA - Ahmed Mohammed, Abdulla (International Journal of Research -GRANTHAALAYAH, 2015)
Many studies were conducted to identify determinants of adoption of crop base technologies and practices and improved seeds, and while few studies concerned on evaluation of extension services in terms of the clients’ need and interest or adoption of livestock technologies in agro-pastoral and pastoral context. In fact, livestock extension services in general in developing countries are less prioritized and thus livestock based technology services are rarely extended. Common livestock technologies which are promoted to livestock raisers are focused on feed, veterinary services, and improved management practices through the extension services of agricultural/pastoral offices and livestock development units. The case hereunder, is about agro-pastoralists extension services evaluative perception and small ruminant fattening package adoption. Hence, this study investigates agro-pastoralists’ perception on the extension services, small ruminant fattening package and intensity of adoption of small ruminants’ fattening package. The study is undertaken in DugdaDawaWoreda, Oromia Region, Ethiopia. The Woreda has agro-pastoral and pastoral production system. The data were collected from 151 randomly selected pastoralists and agro-pastoralists using structured interview schedule. Secondary data were collected from different sources to supplement the data obtained from the survey. In addition to quantitative data qualitative data also gathered. Prior to formal survey an informal survey was also undertaken by using group discussion and interview with key informants. Descriptive statistics such as frequency, percentage mean, standard deviation, Chi-square tests and t-test were employed. The Tobit model was also employed to determine factors influencing intensity of small ruminant fattening package adoption. This study identifies agro-pastoralists and pastoralists are poorly addressed and their need and interests are not considered in any extension programmes. The Tobit model output showed that, agro-pastoralists intensity of adoption of small ruminant fattening package is influenced by: perception on the availability of improved breed, perception on resources based conflicts, current management practices, total livestock holding of HHs and credit use and availability for veterinary purposes. Future extension activities and agencies, promoting fattening package in agro-pastoral and pastoral areas, should focus on targeting agro-pastoralists with low perception on the availability of better breed, information and demonstration on the improved management practices, revision of credit supply criteria, making awareness and demonstration of the significant importance of small ruminants in the agro-pastoral and pastoral income and livelihoods contribution is important.